Identifikasi Pengenalan Pola Daun Kelor Kering Dengan You Only Look Once V8 - Jumariana, I Putu Candra; Sugiartawan, Putu (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2024)
Optimal drying of Moringa oleifera leaves plays an important role in maintaining nutritional quality and meeting desired pattern recognition standards. This research proposes the use of You Only Look Once (YOLO) V8, an object identification method in computer vision, to identify the drying level of Moringa leaves in real-time. The integration of a camera in the drying machine allows visual monitoring of changes in moringa leaves during the drying process. YOLOv8 was implemented to recognize and track changes in moringa leaf dryness levels, enabling timely analysis. The identification results are then classified into dry "YES" or "NO" conditions according to quality standards. This research aims to increase production efficiency, real-time quality monitoring, and ensure Moringa leaf products meet established quality standards. By using the YOLOv8 method, it is hoped that this research will provide an innovative and effective solution in overcoming the challenge of optimally drying Moringa leaves.